Analytic network process approach for locating undesirable facilities:: An example from Istanbul, Turkey - Tuzkaya, Guelfem; Onut, Semih; Tuzkaya, Umut R.; Gulsun, Bahadir (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2008)
Locating an undesirable facility is a sophisticated problem. for the evaluation procedures involve several objectives and the solution to the problem calls for some compromises to be made between probable conflicting criteria. This paper addresses the problem of Undesirable facility, location selection using the analytic network process (ANP), a. multi-criteria decision-making technique. The ANP technique enables LIS to consider both qualitative and quantitative criteria as well as the interdependencies and feedbacks. A number of criteria (benefits, opportunities, costs and risks) and their sub-criteria are considered for siting a new facility with which this Study has dealt. The questions of what criteria Would be considered and what the interdependencies between these criteria and their weights Would be were discussed and determined via interviews with Some competent authorities of the Istanbul Municipality and of two environmental organizations. Four representative locations were evaluated and the most convenient one was selected. This was followed by the sensitivity analyses of the results. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: undesirable facility; location selection; multiple criteria decision making; analytic network process; SUPPLY CHAIN MANAGEMENT; HAZARDOUS-WASTES; PROJECT SELECTION; DECISION-ANALYSIS; SITE SELECTION; MODEL; ANP; SYSTEMS; ALTERNATIVES; LOGISTICS; Environmental Sciences & Ecology